(untitled) (Journal of Geography and Environmental Management, 2017)
This article deals with accidents at the construction site and their causes. The purpose of scientific research is to determine the causes of accidents, to consider ways to reduce them.The scientific and practical importance of the work is to coordinate the workers to ensure security.The main causes of accidents at the enterprise FM «Куrylys» for 2014-2015 are given. The occurrence of accidents is determined by using the statistical method of studying accidents during construction.As the results showed, 70% accidents occur from the activities of employees. According to the conclusion, employees with employment in construction organizations, without fail, must be instructed on TB and comply with safety rules in the workplace.